Factors that influence satisfaction towards frog virtual learning environment among champion secondary school teachers in Southern Region of Malaysia - Cheok, Mei Lick (2018)
The focus of the study was to investigate factors that influence satisfaction towards the FROG Virtual Learning Environment (VLE) in the teaching and learning among the Champion Secondary Schools teachers. It is imperative for MOE to determine the factors that predicts satisfaction towards FROG VLE due to its implications to teachers’ continuous usage of the system. It has been reported that there is an association between user satisfaction and a continued usage of an e-learning system. This would help e-learning developers, MOE, school administrators and teachers to be more apt in designing strategies that are more likely to increase teachers’ satisfaction, thus continue the use of e-learning. The predictors studied were from three categories; characteristics of the teachers, the system and the organisation. Specifically, the factors studied from each category were computer anxiety, computer attitude and internet self-efficacy for teacher’s characteristics; training, technical support and school management in relation to organisation’s characteristics; and perceived usefulness, perceived ease of use, flexibility and interaction in studying FROG VLE’s characteristics. Use of the FROG VLE was studied as a mediator and gender as a moderator. The study was based on a quantitative method with correlational research design conducted by analysing the statistics of mean, standard deviation, percentage and frequency. The statistical analysis of Structural Equation Modeling (SEM) had used SPSS and AMOS Version 22 in analysing the data. The validity of the instrument was established through a panel of content and language experts. A pilot test was carried out among 64 teachers and the Cronbach Alpha Coefficient was found ranging from .81 to .97. The Confirmatory Factor Analysis (CFA) was conducted in order to test for consistency of constructs and to determine the constructs validity. The study involved 350 respondents from the Champion FROG VLE secondary school teachers from three states, namely, Negeri Sembilan, Melaka and Johor. In selecting the sample, the technique used was the proportionate stratified cluster sampling. Several significant findings emerged from this study. The results attained from the analysis generated a model – the Malaysian Teachers’ Satisfaction Model that could be used to explain factors that affect satisfaction towards the FROG VLE among school teachers. There were five significant paths in influencing Satisfaction which are the Internet Self-Efficacy, Computer Attitude, Training, Flexibility and Use of FROG VLE. Consequently, 86% of the variance in satisfaction was explained by the five variables of the study. Mediation analysis has found the construct Use of FROG VLE to be significant, acting as a partial mediator between Internet Self-efficacy and Satisfaction. Full mediation were found in the relationship between Computer Anxiety, Perceived Usefulness, Perceives Ease of Use, Interaction and School Management on Satisfaction. Gender was found not significant as a moderator between Use and Satisfaction. Factors that were found to influence teachers satisfaction towards FROG VLE include Internet Self-Efficacy, Computer Attitude, Training, Flexibility and Use of Frog VLE. Through the mediation test, it can be concluded that with greater use of the FROG VLE, it would lead variables like Computer Anxiety, Perceived Usefulness, Perceives Ease of Use, Interaction and School Management towards Satisfaction. As gender is not significant as a moderator, no differentiation of trainings is needed between the male and female teachers. Hence, the findings of this research will guide and direct stakeholders into specifically focusing on factors that have direct relevance and influence onto teachers satisfaction towards the FROG VLE. As satisfaction will ensure continued use of the system, this in turn will help to further build teachers’ pedagogical skills and techniques in teaching through the FROG VLE. The hope for a more sophisticated utilisation of technology across the schools would then be realised. This will also benefit and yield greater returns to the Ministry of Education in line with the investment made towards the virtual learning initiative for classroom teaching and learning.